Alternative documakers: strange forces at work - Badrul Redzuan Abu Hassan,; Roslina Abdul Latif, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Documentary film has established itself as an important spatial extension of this nation's historicity. This paper explores the terrains of this critical transformational space which in recent years, has been dominated arguably increasingly, by a cohort of 'socialist' filmmakers. That such an 'alternative/independent' group of documakers - a label it is often associated with - edges over the 'mainstream' ones in terms of its worthiness, timeliness and relevance of an issue, debate or perspective, is a claim or perception that needs to be qualified in this paper. Notable documakers gave in-depth interviews on their creative works and issues of nation building both in shaping the trajectory of ‘alternative’ documentary, hence, sustaining a potentially transformative public sphere. This paper will engage in analyzing critical and defining documentary works as its mode of inquiry followed by the discourses gleaned from the interviews.